Political and Institutional Characteristics of the Entry of the CEE Region into Regional Media Systems During the Bipolar and Post-Bipolar Periods - Vitaliy Tereshchuk (Ksiegarnia Akademicka Publishing, 2019)
In the newly shaped post‑WWI Europe the CEE region was an integral part of the pan‑European media system. The iron curtain that split Europe into two parts in the bipolar period, inevitably led to the emergence of two separate media systems, i.e. the Western European one and the one driven by the USSR (and existing predominantly in Eastern‑European states). These systems were institutionalized by the establishment of separate broadcasting alliances and corresponding TV programme exchange networks. At the same time, in the context of the Cold War, the CEE region was a key target of Western broadcasting with the aim to counter Soviet propaganda and political influence. This factor reinforced by the willingness of the CEE countries to preserve their European identity caused the socialist media system (as well as other Soviet integration projects) to remain artificial and to be rejected in the region. It was clearly confirmed at the beginning of the post‑bipolar period, when, after the collapse of the socialist camp and the USSR, the Soviet‑driven International Radio and Television Organization ceased to exist, and the CEE countries integrated into the European Broadcasting Union, unleashing their desire to “return to Europe”. At the same time, in the context of a policy aimed at preserving control over the post‑Soviet space, Russia makes efforts which could be regarded as an attempt to restore (preserve) the common media space in the post‑Soviet territories. In the paper the CEE region is regarded in the broadest way, including all states which were in socialist bloc, and appropriate former European Soviet republics.